The nature and origin of acronyms in Kiswahili and Setswana (JULACE: Journal of the University of Namibia Language Centre, 2018)
This study examines how this mechanism has been used in two major regional languages, namely Kiswahili, spoken in eastern Africa, and Setswana, extensively used in southern Africa. The main aim of the article is to investigate how these two regional languages have dealt with the influx of acronyms which have become important word forms in African languages, as the use of these languages expands to higher domains. The study uses primary and secondary data to demonstrate the efforts which have been made in the development of acronyms in both languages, and the challenges which have been experienced. The study findings are very revealing in that they show that, although most African dictionaries do not include acronyms as part of their entries, they are found most often in the higher domains and appear in many forms. The main conclusion of the paper is that African countries need full-fledged language institutions and supportive language policies in order to spearhead the process of lexical expansion and intellectualization of the indigenous African languages by using all strategies of term development.